Language Ideologies: Family Language Policies on Bi/Multilingualism - Rani Septi Sapriati (LINGUA: Jurnal Bahasa dan Sastra, 2020)
Abstract: English is the most useful language to be mastered in this century of globalization, but it has no particular official position in Indonesia. It was claimed as the first foreign language in Indonesia whose status as a multilingual country. In terms of being able to compete with others in this era, the citizen must have the ability to use English. As a result, the family has a substantial responsibility to educate their children bi-/multilingually, using two or more languages in interaction, especially using English. Parents do a role to undertake in constructing language policy in the family, what they wholeheartedly believe in languages (ideologies), how languages are exerted (practices), and what attempts have been made to retain languages (management). Focusing on this community, a conceptual framework for language ideologies held by bi/multilingual families is provided in this paper: cultural values, political values, social values, economical values, values of language acquisition, and parents' knowledge toward bi/ multilingualism. Keywords: Bi-/multilingualism, family language policy, language ideologies Abstrak: Bahasa Inggris merupakan bahasa yang paling berguna untuk dikuasai di abad globalisasi ini, tetapi tidak memiliki posisi resmi tertentu di Indonesia. Bahasa Inggris diklaim sebagai bahasa asing pertama di Indonesia yang berstatus negara multibahasa. Agar mampu bersaing di era ini, warga negara harus memiliki kemampuan berbahasa Inggris. Oleh karena itu, keluarga memiliki tanggung jawab yang besar untuk mendidik anak-anak mereka menggunakan dua bahasa atau lebih dalam interaksi, khususnya menggunakan bahasa Inggris. Orang tua berperan dalam membangun kebijakan bahasa di keluarga, apa yang mereka yakini sepenuh hati terhadap bahasa (ideologi), bagaimana bahasa digunakan (praktik) dan upaya apa yang telah dilakukan untuk mempertahankan bahasa (manajemen). Berfokus pada komunitas ini, kerangka konseptual ideologi bahasa yang dipegang oleh keluarga dua atau multibahasa disajikan dalam tulisan ini: nilai budaya, nilai politik, nilai sosial, nilai ekonomi, nilai pemerolehan bahasa dan pengetahuan orang tua terhadap dua atau multibahasa. Kata-kata Kunci: Dua atau multibahasa, kebijakan bahasa keluarga, ideologi bahasa